Integrated engineering geological evaluation of Proterozoic sandstones: a case study of the construction site near the town of Udokan - T. G. Ryashchenko; S. A. Tyrshih; T. A. Kornilova; E. V. Bryzhak (Известия высших учебных заведений: Геология и разведка)
The article considers the results of integrated engineering geological studies of Proterozoic sandstones at the construction site near the town of Udokan. The «Standard Statistics» and «Cluster Analysis» programs have been applied by processing the data on density, strength and water resistance of the soils obtained during the research. The samples have been examined for water absorption and longitudinal seismic wave velocity, the structural and textural characteristics of rocks in petrographic thin sections have been studied for the first time. On the basis of complex data, conclusions about the strength factors of the studied objects have been drawn out.